Ma’had Al-Zaytun Artikulasi Ke-Islaman Dan Ke-Indonesiaan Di Pendidikan Pesantren - taufik nugroho (Universitas Cokroaminoto Yogyakarta, 2020)
The research aims to reveal Ma’had Al-Zaytun as an Islamic educational institution in the aspects of ideology, direction and goals of education. The importance of this research is because a growing issue in society says that Ma’had Al-Zaytun carries a hidden agenda of